2020
DOI: 10.1016/j.drugalcdep.2020.108004
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary wheel running protects against the increase in ethanol consumption induced by social stress in mice

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 105 publications
(110 reference statements)
2
19
0
Order By: Relevance
“…It is well known that physical exercise inhibits the activation of NF-κB signal caused by inflammation [22,23]. In particular, voluntary wheel exercise in rodents induces changes in several signaling molecules by inhibiting the stress-related behavior compared to forced exercise [24,25]. In the current study, voluntary wheel running reduced IκB-α phosphorylation, resulting in NF-κB inactivation.…”
Section: Discussionsupporting
confidence: 48%
“…It is well known that physical exercise inhibits the activation of NF-κB signal caused by inflammation [22,23]. In particular, voluntary wheel exercise in rodents induces changes in several signaling molecules by inhibiting the stress-related behavior compared to forced exercise [24,25]. In the current study, voluntary wheel running reduced IκB-α phosphorylation, resulting in NF-κB inactivation.…”
Section: Discussionsupporting
confidence: 48%
“…Using the oral alcohol self-administration paradigm, an increase in consumption and motivation to obtain the substance have been observed in defeated animals. Moreover, this effect is maintained several months after the last social defeat (Reguilón et al, 2020). Similar results have been shown in mice subjected to social defeat during adolescence (Rodríguez-Arias et al, 2016).…”
Section: ■ Social Stress Makes Us Drink More Alcoholsupporting
confidence: 85%
“…Another critical time is during the rehabilitation process, where social stress can easily induce relapse. Preclinical studies support the outcomes observed in humans and show that exposure to social defeat increases alcohol intake compared to non-stressed animals (Reguilón et al, 2020). Using the oral alcohol self-administration paradigm, an increase in consumption and motivation to obtain the substance have been observed in defeated animals.…”
Section: ■ Social Stress Makes Us Drink More Alcoholmentioning
confidence: 55%
“…After SD, increases in the acquisition of and motivation to take cocaine has been extensively reported using the SA procedure [153][154][155][156]. Equally, defeated mice show higher ethanol intake in the oral SA paradigm [61,76,157,158]. Studies using the CPP paradigm have also shown an enhancement in the conditioned rewarding effects of cocaine and ethanol in stressed animals [73,[158][159][160][161].…”
Section: Oxytocin Blocks Increased Drug Intake Induced By Social Defeatmentioning
confidence: 95%
“…Equally, defeated mice show higher ethanol intake in the oral SA paradigm [61,76,157,158]. Studies using the CPP paradigm have also shown an enhancement in the conditioned rewarding effects of cocaine and ethanol in stressed animals [73,[158][159][160][161]. Both the aforementioned paradigms permit a broad assessment of the rewarding effects of drugs of abuse as both measure the role of motivation and environmental cues [162,163].…”
Section: Oxytocin Blocks Increased Drug Intake Induced By Social Defeatmentioning
confidence: 99%